Shariah Framework for the Real Estate Industry in Pakistan: A Jurisprudential Analysis of Contemporary Property Transactions - Muhammad Noman; Muhammad Adil Ayub; Iftikhar Ud Din (`, 2025)
Pakistan’s property market grows fast. Yet behind rising deals lies a tangle of actions that often ignore Islamic law. Classical teachings on finance offer clear guidance, yet many current methods drift far from these roots. This piece looks closely at how land and buildings change hands today. It checks modern deals against old rules and decisions made by trusted religious bodies in Pakistan. Four types of dealings take center stage. First, buying and selling plots, apartments, or shops - often done without proper ownership transfer. Second, middlemen who arrange sales for pay, raising questions about fairness and transparency. Third, payment plans spread over time where price changes spark debate on interest-like gains. Fourth, builder contracts shaped like istis̱n̄a - a form meant for custom building but now twisted beyond intent. Many common moves fall short of religious standards. Selling paper rights too early, bribing officials to speed up paperwork, flipping assignment slips for quick profit - all break boundaries set long ago. Even so-called discount offers tied to early full payments hide debt traps forbidden under faith-based rules. For every gap found, another way opens - one rooted in honesty, clarity, and duty - not just money flow. Each flawed practice meets a match grounded in older wisdom rebuilt for present needs. Despite its roots in ancient doctrine, classical Islamic commercial law can adapt to today’s real estate demands - yet shifts in how deals are made, contracts written, and rules enforced remain critical for Pakistan to meet its constitutional duties under Islam. Rather than dwell on theory, this piece builds a practical model rooted in the Ḥanafī school, which shapes most legal thinking in the country, adding to ongoing conversations about faith-based finance and land rights. Keywords: Shariah, real estate, bay' (sale), istiṣnā', ijārah, wikālah, taqsīṭ, fiqh al-mu'āmalāt, Pakistan, Islamic finance, property transactions